MESSA A PUNTO E VALIDAZIONE DI UN PROTOCOLLO PER L’ESTRAZIONE DI MICROPLASTICHE DAL VERME DI FUOCO HERMODICE CARUNCULATA (ANNELIDA) - Ferrari, Valentina (Biologia Marina Mediterranea, 2024)
Microplastic pollution in the marine environment has raised high concern over the last years. An increasing number of studies have dealt with microplastic ingestion as it constitutes a hazard to marine organisms. However, information about some mediterranean benthic species, such as polychaetes, is still limited. Here, a tissue digestion method to extract microplastics from the fireworm Hermodice carunculata has been developed and the details are presented. Filterability, digestion effectiveness, recovery of microplastics and the reagent-dependent damage on common polymer types were assessed. The proposed protocol showed high efficiency on organic matter removal while preserving the structural integrity of the plastic polymers. Our results can be useful for standardizing the identification and quantification procedures of microplastics ingested by other polychaete species.